Canva Animated Video Improves Elementary Social Studies Comprehension: Video Animasi Canva Meningkatkan Pemahaman Mata Pelajaran Sosial di Tingkat Sekolah Dasar - Anggraeni, Wahyu; Wati, Tri Linggo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Digital learning media play a crucial role in addressing low engagement and conceptual difficulties in elementary Social Studies education. Specific Background: Social Studies material on international cooperation requires visual and contextual representation to support students’ understanding of abstract concepts. Knowledge Gap: Although animated video media have been widely discussed, limited studies have systematically developed and validated Canva-based animated videos using a structured ADDIE model for sixth-grade Social Studies content. Aims: This study aims to develop and evaluate a Canva-based animated video to improve elementary students’ comprehension of international cooperation material. Results: Using the ADDIE development framework, the product was validated by material and media experts and categorized as very feasible. Implementation results showed a significant increase in student scores, with the average pretest score of 67.69 rising to 90.96 in the posttest and an N-Gain value of 0.720 classified as high. Novelty: The study presents a validated instructional design integrating visual animation, narration, and structured development stages tailored to Social Studies content. Implications: The findings demonstrate that Canva-based animated video supports conceptual clarity and measurable learning progress in elementary Social Studies classrooms. Keywords: Animated Video, Canva, Social Studies Education, ADDIE Model, Student Comprehension Key Findings Highlights: Expert validation indicated very high feasibility levels. Classroom trials demonstrated substantial score progression. Visual narration facilitated clearer understanding of cooperation concepts.